2012
DOI: 10.1111/j.1462-5822.2012.01752.x
|View full text |Cite
|
Sign up to set email alerts
|

Newly visualized fibrillar collagen scaffolds dictate Entamoeba histolytica invasion route in the human colon

Abstract: SummaryThe extracellular matrix (ECM) and its role in the outcome of infectious diseases have been poorly investigated. In this study, we determined the impact of the collagen fibres architecture on the invasive process of the enteric parasite Entamoeba histolytica. The behaviour of E. histolytica wild-type and silenced for the cysteine protease A5 (CP-A5) were compared on a three-dimensional collagen matrix and within human colon fragments for fibrillar collagen cleavage and migration. The interstitial collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
55
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 34 publications
3
55
0
Order By: Relevance
“…We controlled the effect of marimastat on E. histolytica by preincubated trophozoites with marimastat 30 min prior the incubation on human colon tissue. Treatment with marimastat alone had no effect on the trophozoites' invasiveness, since marimastat-treated trophozoites subsequently invaded the tissue to the same extent as wild-type (WT) trophozoites 3,4 (Fig. 1a).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…We controlled the effect of marimastat on E. histolytica by preincubated trophozoites with marimastat 30 min prior the incubation on human colon tissue. Treatment with marimastat alone had no effect on the trophozoites' invasiveness, since marimastat-treated trophozoites subsequently invaded the tissue to the same extent as wild-type (WT) trophozoites 3,4 (Fig. 1a).…”
Section: Resultsmentioning
confidence: 98%
“…We had previously shown that intestinal invasion by E. histolytica requires collagen fibre remodelling 4 . Thus, we next looked at whether the inhibition of intestinal invasion in the presence of marimastat was correlated with a defect in collagen remodelling (as a consequence of MMP inhibition).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations